EVALUATION OF COMMUNITY-BASED INTEGRATED CHILD PROTECTION PROGRAM (PATBM) IN MAROS DISTRICT - Erviana, Irna; Sakawati, Herlina; Aslinda, Andi; Fitri, Anisa (Jurnal Aktor, 2025)
This research aims to understand the Policy Evaluation of the Community-Based Integrated Child Protection (PATBM) program by considering geographical variations in Maros Regency. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation studies. The validity of the data was checked through diligent observation and triangulation of sources. Data analysis is carried out through the stages of data collection, data condensation, data presentation, and drawing conclusions or verification. The results of this research indicate that the Evaluation of the Community-Based Integrated Child Protection Program (PATBM) takes into account geographical variations in Maros Regency, based on six William N. Dunn Policy Indicators (2003), namely: 1) Effectiveness, 2) Efficiency, 3) Coverage, 4 ) Alignment, 5) Responsiveness, 6) Accuracy, Quite optimal level of effectiveness in mountainous and coastal areas. With a minimal budget, the program still achieved its goals, showing good efficiency. The eligibility criteria are also met, with PATBM becoming an alternative solution to the problem of child violence. In terms of alignment, this program has been evenly distributed. Apart from that, the PATBM program is considered quite responsive to community needs and meets the responsiveness criteria and this program is also appropriate, but needs improvement in the monitoring and evaluation (monev) process